Síntese e análise estrutural de compostos derivados de calcogenolatos metálicos MER (M = HgII, PdII; E = Se, Te; R = aril) - Tirloni, Bárbara (2013)
This work presents a study related to the synthesis and structural analysis of compounds derivatives from metal chalcogenolates - MER (M = HgII, PdII; E = Se, Te; R = aryl). In the first step of this work were investigated reactions of Hg(SePh)2 with HgII halides, that led to the formation of a series of binary compounds. In the second step, it was planned to obtain heterometallic compounds, with the incorporation of a second metal (M) in the structure of the compound. For this, we explored reactions of Hg(TeR)2 (R = Ph, Mes, (2,6- OCH3)2C6H3) with different PdII salts. These reactions led to the formation of one ternary compound HgTePd and four binary compounds, whereas three of them have the core made up of TePd and one of TeHg. In the third step, this work was focused on exploring reactions of (ER)2 with PdII and HgII salts. These reactions led to the E-E bond cleavage and the formation of compounds derivatives from metal chalcogenolates with different structures. A structural study in the solid state of all compounds was carried out using single crystal Xray diffraction. Other analytical methodologies such as elemental analysis and infrared spectroscopy were also used for the characterization of the compounds. The ultraviolet-visible spectroscopy supported the measurement of the optical band gap in the solid state for the compounds obtained.